2017
DOI: 10.3390/w9050299
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity of Soil, Rock and Water in a Shale Gas Exploitation Area, SW China

Abstract: Abstract:Studies have been carried out to investigate the baseline radioactivity level (gross alpha, gross beta and 226 Ra) of soil, rocks and groundwater in the Fuling block, Chongqing, the largest shale gas exploitation area of China. The results show that there is a general activity concentration trend of gross alpha, gross beta and 226 Ra: shale > soil > limestone due to the high content of uranium, thorium and potassium in shale and low content in limestone. The average activities of shallow groundwater f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…There are no guideline levels for limit values for GA and GB activity concentrations in soil and sediment to compare the obtained results and to evaluate hazards to the population. However, when the GA and GB activity concentrations were compared with other studies, these activities were found to be higher than the similar studies [56-58] and some of them were low [59].…”
Section: Chemical and Radiological Resultscontrasting
confidence: 60%
“…There are no guideline levels for limit values for GA and GB activity concentrations in soil and sediment to compare the obtained results and to evaluate hazards to the population. However, when the GA and GB activity concentrations were compared with other studies, these activities were found to be higher than the similar studies [56-58] and some of them were low [59].…”
Section: Chemical and Radiological Resultscontrasting
confidence: 60%
“…As mentioned in introduction, the underlying geological formation is one of the important factors that affect the radionuclide level in thermal water sources. In the current case, the geological characteristic at the thermal water sources are similar, and the underlying limestone aquifer has relatively low activity concentrations [10,20,21].…”
Section: Resultsmentioning
confidence: 92%
“…Areas with high background radiation concentrations such as granite, phosphate, shale formations can have elevated levels of radioactivity in ground or thermal waters [47][48][49][50]. On the other hand, areas with low natural radioactivity are often found in carbonate or limestone formations, which often correspond to lower levels of natural radioactivity in the water resources in those areas [44,[51][52][53][54][55][56]. In this study, the 210 Po characteristics in the thermal water at these eight sites is a case study for an area believed to have a low radioactive background with a carbonate host formation.…”
Section: Resultsmentioning
confidence: 99%